Experimental Investigation of 137Cs aging in soil - Assimakopoulos, P. A.; Ioannides, K. G.; Karamanis, D. T.; Pakou, A. A.; Stamoulis, K. C.; Vayanakis, A.; Veltsos, E. (HNPS Advances in Nuclear Physics, 2019)
No abstract (available).